Death in the monastery: Dying in the poetry of a Carthusian monk - Hujanen, Riitta ca. 20./21. Jahrhundert (Scottish journal of theology, 2025)
"Death in the monastery" refers to liminal and temporal themes of dying in the poetry of an anonymous Carthusian monk-poet in the period 1964-2024. This article explores these topics in three subsections. The first section deals with texts where the monk-poet reflects on moments when he has witnessed the dying of a fellow monk. The second set of texts focuses on memories written about recently deceased members of the Carthusian monastic community. The third section consists of the Carthusian author's reflections that arise from the physical proximity of the graveyard at the centre square of the monastery. The article concludes with some remarks on the liminal and temporal perspectives on dying in a monastery. Time spent with God in a cloister, while frequently witnessing the deaths of other members of the monastic community, prepares for a transition where death is followed by resurrection.